Phytochemical Constituents, Antioxidant and Antiproliferative Properties of a Liverwort, Lepidozia borneensis Stephani from Mount Kinabalu, Sabah, Malaysia. (11th November 2015) - Abu Bakar, Mohd Fadzelly; Abdul Karim, Fifilyana; Suleiman, Monica; Isha, Azizul; Rahmat, Asmah
Abstract : The study aimed to investigate the phytochemical contents, antioxidant and antiproliferative activity of 80% methanol extract of Lepidozia borneensis . The total phenolic and total flavonoid contents were analysed using Folin-Ciocalteu and aluminium chloride colorimetric methods. Antioxidant properties were evaluated by using FRAP, ABTS, and DPPH assays while the effects of L. borneensis on the proliferation of MCF-7 cell line were evaluated by using MTT assay. The results showed that the total phenolic and flavonoid contents were 12.42 ± 0.47 mg GAE/g and 9.36 ± 1.29 mg CE/g, respectively. The GC-MS analysis revealed the presence of at least 35 compounds. The extract was found to induce cytotoxicity against MCF-7 cell line with IC50 value of 47.33 ± 7.37 µ g/mL. Cell cycle analysis showed that the extract induced significant arrest at G0 /G1 at 24 hours of treatment. After 72 hours of treatment, the proportion of cells in G0 /G1 and G2 -M phases had decreased significantly as compared to their control. Apoptosis occurred during the first 24 hours and significantly increased to 30.8% after 72 hours of treatment. No activation of caspase 3 was observed. These findings suggest that L. borneensis extract has the potential as natural antioxidant and anticancer agents.